Coffee research network for Africa - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1992)
CTA, together with the Inter-African Coffee Organization (IACO), organized a seminar on Promoting Research on the Productivity and the Quality of Coffee in Africa. This meeting was held in Lisbon from 22-26 June 1992